PROSES CETAK BRIKET BERBAHAN LIMBAH KOLANG-KALING DENGAN TEKNOLOGI TEPAT GUNA - Supriyadi, Supriyadi; Masturi, Masturi; D.J., Pratiwi (Rekayasa : Jurnal Penerapan Teknologi dan Pembelajaran, 2015)
Has carried out activities to the community in the form of the development of the printing press in the village briquettes Jatireo Gunungpati Kodia subdistrict in Semarang. The background of this activity is to address the process of making briquettes at the time of printing, where the results obtained are not crowded so long the flame is not as expected. To overcome these problems have created a tool that is used to press briquettes load prior to release of the molding tool. The results showed no difference in the thickness of the pressed briquettes are pressed. The thickness of the briquettes without using the press is 1 cm and 0.5 cm using a press. In addition, test results obtained by burning briquettes burning rate of the skin and fro in the range of 0.03 to 0.04 g/s. This result is consistent with the type of biomass briquettes from other types such as wood, leaves, etc. with 0.03 combustion rate g/s. The color of the flame indicated when laboratory testing is reddish yellow and the smoke does not cause itching when on the skin.